Fall‐armyworm invasion, control practices and resistance breeding in Sub‐Saharan Africa. Issue 6 (11th November 2020) - Matova, Prince M.; Kamutando, Casper N.; Magorokosho, Cosmos; Kutywayo, Dumisani; Gutsa, Freeman; Labuschagne, Maryke
Abstract: Fall armyworm [ Spodoptera frugiperda (J.E. Smith); FAW] invasion has exacerbated maize ( Zea mays L.) crop yield losses in sub‐Saharan Africa (SSA), already threatened by other stresses, especially those that are climate‐change induced. The FAW is difficult to control, manage, or eradicate, because it is polyphagous and trans‐boundary, multiplies fast, has a short life cycle and migrates easily, and lacks the diapause growth phase. In this study, FAW and its impact in Africa was reviewed, as well as past and present control strategies for this pest. Pesticides, cultural practices, natural enemies, host‐plant resistance, integrated pest management (IPM), and plant breeding approaches were examined as possible control strategies. It was concluded that an IPM control strategy, guided by cultural approaches already being used by farmers, and what can be adopted from the Americas, coupled with an insect‐resistance management strategy, is the best option to manage this pest in Africa. These strategies will be strengthened by breeding for multi‐trait host‐plant resistance through stacking of genes for different modes of control of the pest.